Nasal Reflux Management of Obturator in Dentate Maxillectomy Patients - Rezeki, Ariyanti; Marito, Pinta (Indonesian Dental Association, 2020)
Introduction: Maxillary defects are probably the most common of all intraoral defects. Moreover, their size and location affect the degree of difficulty in prosthetic rehabilitation. Maxillary defects may be divided into two types: (i) defects resulting from congenital malformations and (ii) acquired defects resulting from surgery for oral neoplasms. Acquired maxillary defects in the form of postsurgical defects can cause conditions such as nasal voice (hypernasal speech), nasal cavity leakage, mastication function deterioration, and considerable facial collapse due to extensive bone loss. Case Report: A 34-year-old male patient with resection—without prior surgical or interim obturator placement—performed in 2018 on the premaxillary segment and anterior maxillary alveolar ridge came to the Department of Prosthodontics, Faculty of Dentistry, Universitas Indonesia (Depok, Indonesia). The prosthetic rehabilitation goals for this case included the separation of oral and nasal cavities to allow adequate deglutition and articulation, possible support of the orbital contents to prevent enophthalmos and diplopia, support of the soft tissue to restore the midfacial contour, and an acceptable aesthetic result. In this clinical report, a maxillary obturator prosthesis framework was used as a definitive treatment. Conclusion: A proper and detailed treatment sequence is critical for successful prosthetic rehabilitation of a dentate maxillectomy patient. A considerably successful maxillary obturator indicator, such as masticatory function and distinct speech, was regained. The nasal cavity leakage problem was solved after sealing the gap between the oral and nasal cavities by providing adequate extensions of the flange.